Retrieval of a Dislodged Catheter Using Combined Fluoroscopy and Intracardiac Echocardiography - Gus Mitsopoulos; Robert F. Hanna; Sidney Z. Brejt; Greg E. Goldstein; Vladimir Sheynzon; Joshua L. Weintraub; William A. Gray (Case Reports in Radiology)
This report details a method of percutaneous, transluminal retrieval of an intracardiac foreign body using fluoroscopy in combination with intracardiac echocardiography. During retrieval, intracardiac echocardiography (ICE) provided real-time anatomic localization of a constantly moving, almost radiolucent micropuncture coaxial dilator fragment with respect to the tricuspid and pulmonary valves. This method may serve as a crucial aid in retrieval of intracardiac foreign bodies that are difficult to see with fluoroscopy and which may be adjacent to cardiac valves.